CHARACTERISTICS OF POTENTIALLY HAIL-PRODUCING CLOUDS USING ADVANCED HIMAWARI IMAGER (CASE STUDY: JAVA ISLAND) - Mohd Imanuddin Abdurrahman, Kms
Cloud structure and distribution of hail cases in Java Island within month of February 2019 were observed using Advanced Himawari Imager true-color. Cloud characteristics was analysed using Himawari-8 AHI true-color, brightness temperature (BT) of band 13, and brightness temperature difference (BTD) using band 7, 8, 10, 13. The observed characteristics were distance of cloud top relatively from level of tropopause (BTD band 8-10), cloud top temperature (BT band 13), and composition of cloud (BTD band 7-13). Temporal analysis of those characteristics shown indication of strong updraft. BTD band 8-10 showed sudden changes of increasing cloud-top height while decreasing cloud-top temperature shown by BT band 13. Those sudden changes lead to an increase of ice particle from cloud pointed out by BTD band 7-13. The strong updraft is indicated also by the existence of overshooting top. Strong updraft with overshooting top lift water vapor and ice particles to higher and colder level through low troposphere.